2020
DOI: 10.1021/acsomega.9b03229
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery Efficiency and Mechanism of Low Salinity-Enhanced Oil Recovery for Light Crude Oil with a Low Acid Number

Abstract: Low salinity waterflooding (low salinity-EOR) has attracted great interest from many giant oil producers and is currently under trial in some of the oil fields of the United States, Middle Eastern countries, and North Sea reservoirs. Most of the reported studies on this process were carried out for medium to relatively heavy oil with significant polar contents. In this work, we have investigated low salinity waterflooding performance for light paraffinic crude oil with a low acid number. This study has been pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…The increasing oil recovery during secondary water flooding from HSPF to LSPF #3 clearly indicates the oil recovery potential of low salinity water flooding. Data reported in our previous study indicated that a reduction in oil–water interfacial tension and a change in reservoir rock wettability are the primary mechanisms of low salinity enhanced oil recovery . It was also observed that the oil recovery was a maximum in the case of 25% seawater, as interfacial tension and wettability states were most favorable at this salinity.…”
Section: Results and Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The increasing oil recovery during secondary water flooding from HSPF to LSPF #3 clearly indicates the oil recovery potential of low salinity water flooding. Data reported in our previous study indicated that a reduction in oil–water interfacial tension and a change in reservoir rock wettability are the primary mechanisms of low salinity enhanced oil recovery . It was also observed that the oil recovery was a maximum in the case of 25% seawater, as interfacial tension and wettability states were most favorable at this salinity.…”
Section: Results and Discussionmentioning
confidence: 55%
“…Data reported in our previous study indicated that a reduction in oil−water interfacial tension and a change in reservoir rock wettability are the primary mechanisms of low salinity enhanced oil recovery. 88 It was also observed that the oil recovery was a maximum in the case of 25% seawater, as interfacial tension and wettability states were most favorable at this salinity. A lower interfacial tension at low salt concentration is due to the surface excess of aqueous ions which preferentially move to the oil−water interface by dipole-induced dipole interaction.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…With the development of science and technology, the range of vibration intensity (increasing) and frequency (decreasing) of a hydraulic vibrator is gradually expanding and improving. 24 At the same time, with the aid of automation technology, acidizing, hydraulic fracturing, and other enhanced stimulation measures, the near-well treatment effect of this method has been further strengthened. 25 …”
Section: Introductionmentioning
confidence: 99%
“…Low salinity water flooding is a quite new technique, implemented to adjust the salt content in sea water before injection to the reservoir. Therefore it has been considered by various research groups as one of the most inexpensive techniques of EOR [5,6] and has been reported for both laboratory core floods and field tests [7][8][9][10]. The combination of low salinity water injection and surfactant flooding (LSW-SF) is considered to be an economically attractive EOR approach, as high oil recovery and low surfactant retention was reported in core flooding tests [11].…”
mentioning
confidence: 99%